UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN PATIKAN KEBO (Euphorbia hirta L) TERHADAP Staphylococcus aureus dengan METODE DIFUSI CAKRAM - Habib Abdul Muiz; Shinta Wulandari; Annisa Primadiamanti (Jurnal Analis Farmasi, 2022)
Patikan kebo (Euphorbia hirta L) is a grass-shaped plant and is often used as a traditional medicine by the community. The people of Pasir Sakti use patikan kebo as a medicine for skin infections. Skin infection is the most common disease caused by Staphylococcus aureus bacteria. Based on research by Harlis 2010 patikan kebo leaves has active compounds of flavonoids and tannins that can inhibit bacterial growth. This study aimed to examine the potential of patikan kebo leaf extract in inhibiting the growth of Staphylococcus aureus bacteria using variants of the concentration of patikan kebo leaf extract, namely 30%, 40%, 50%, and 60%. Tetracyline as positive control and sterile distilled water as negative control. Antibacterial activity test was carried out by disc diffusion method. Based on the results of the inhibition test with three repetitions, the consentration of 30% has inhibition zone of 10.48 mm, the concentration of 40% has inhibition zone 12.26 mm, the concentration of 50% has inhibition zone 14.32 mm, and the concentration of 60% has inhibition zone of 15.26 mm. The conclusion of this study, patikan kebo leaf extract has antibacterial activity against the growth of Staphylococcus aureus bacteria.